Analysis of the Use of The Complete Clause in the Daily Newspaper Titled 'Families of Victims of the Lingga Kencana Vocational School Accident' - Amelia Afriani; Yusni Khairul Amri (Britain International for Academic Research (BIAR-Publisher), 2024)
This research aims to study the format of the Detik News daily article for the 12 May 2024 edition. The clause form studied is a complete clause, where a complete clause is a grammatical unit consisting of a subject and a predicate, and has the potential to become a sentence, although not always. This complete clause can stand alone without needing to be combined with other clauses. The data collection technique used was by listening and taking notes in the daily newspaper Detik News entitled